Forward engineering of public institutions in market economy: Towards a new theory of public administration - Sharma, Subhash (1996)
Presenting basis for evolving a theory of empowerment in the market context, the author argues that the theory is tied to the theory of markets, and arises from consequence effects of markets. To explain this link, he discusses market behaviour using three models. He argues that a shift from "empire" model to "umpire" model necessitates a new theory of Public Administration that incorporates within its realm development partnership and empowerment roles of the State. He also suggests that institution-building for empowerment being a key theme of forward engineering of public institutions in the market economy, the theory can be used for forward engineering of public institutions around new roles of umpiring,developing partnership and empowering persons living on the market's blunt edge. - Reproduced
Keywords: Public administration